2016
DOI: 10.1002/ece3.2139
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary ecology of pipefish brooding structures: embryo survival and growth do not improve with a pouch

Abstract: For animals that reproduce in water, many adaptations in life‐history traits such as egg size, parental care, and behaviors that relate to embryo oxygenation are still poorly understood. In pipefishes, seahorses and seadragons, males care for the embryos either in some sort of brood pouch, or attached ventrally to the skin on their belly or tail. Typically, egg size is larger in the brood pouch group and it has been suggested that oxygen supplied via the pouch buffers the developing embryos against hypoxia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…These results mirror those reported for several Atlantic fish species where high mobility and/or high dispersal potential are highlighted as causes for little or no population sub-structuring (Nesbo, Rueness, Iversen et al, 2000;Dannewitz, Maes, Johansson et al, 2005;Carr & Marshall, 2008;Limborg, Hanel, Debes et al, 2012). Our results suggest that despite having relatively low swimming ability, the snake pipefish is capable of dispersing over long distances, likely aided by a pelagic lifestyle and faster development rates relative to other northeastern Atlantic syngnathid species (Braga Goncalves, Ahnesjö & Kvarnemo, 2016). A similar pattern has been described in the nonmigratory, demersal marine fish, Sebastes schegelii, where the association of larvae and juveniles with rafting precludes population genetic differentiation throughout its geographical range (Zhang, Yanagimoto, Zhang et al, 2016).…”
Section: Population Structuresupporting
confidence: 88%
“…These results mirror those reported for several Atlantic fish species where high mobility and/or high dispersal potential are highlighted as causes for little or no population sub-structuring (Nesbo, Rueness, Iversen et al, 2000;Dannewitz, Maes, Johansson et al, 2005;Carr & Marshall, 2008;Limborg, Hanel, Debes et al, 2012). Our results suggest that despite having relatively low swimming ability, the snake pipefish is capable of dispersing over long distances, likely aided by a pelagic lifestyle and faster development rates relative to other northeastern Atlantic syngnathid species (Braga Goncalves, Ahnesjö & Kvarnemo, 2016). A similar pattern has been described in the nonmigratory, demersal marine fish, Sebastes schegelii, where the association of larvae and juveniles with rafting precludes population genetic differentiation throughout its geographical range (Zhang, Yanagimoto, Zhang et al, 2016).…”
Section: Population Structuresupporting
confidence: 88%
“…We found few effects of egg size on the variables measured in this study. Smaller eggs resulted in more densely packed broods across both male size classes, and in lower embryo mass, which is in line with previous findings (Ahnesjö 1992a,b; Braga Goncalves et al 2016). Egg size did not affect embryo survival nor pouch oxygen saturation levels, consistent with other studies on S. typhle (Mobley et al 2011; Braga Goncalves et al 2015b), but opposed to expectations from theory (Sargent et al 1987; Hendry et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Although this constraint has been argued to pose limits on the evolution of egg size in aquatic environments (Sargent et al 1987; Rombough 1998; Hendry et al 2001; Kolm and Ahnesjö 2005), this view has been increasingly challenged in recent years. Several studies have shown that large eggs do just as well (or better) as small eggs, even under low oxygen conditions (Einum et al 2002; Braga Goncalves et al 2015a,b, 2016; Polymeropoulos et al 2016; Rollinson and Rowe 2018). This is likely to occur if and when embryo oxygen requirements increase more slowly than egg surface area with increasing egg size so that the respiratory consequences of a lower surface-area-to-volume ratio are less pronounced than previously estimated (Einum et al 2002; Braga Goncalves et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The closed pouch may have facilitated polygyny, in which males have the capacity to accept eggs from more than one female (Monteiro et al ., ), although polygyny is also physically possible in open pouches, and many closed‐pouch species are monogamous. Finally, there is growing evidence that brood pouches may be an arena of sexual conflict, in which the closed pouch could give males greater reproductive control (Paczolt & Jones, ; Braga Goncalves, Ahnesjö & Kvarnemo, ; Da Cunha et al ., ).…”
Section: The Evolution Of Male Pregnancymentioning
confidence: 99%